KERANGKA ADVOKASI KOALISI DALAM KEBIJAKAN PENATAAN PEMUKIMAN BANTARAN SUNGAI WINONGO DI KOTA YOGYAKARTA - Harirah, Zulfa (Nakhoda: Jurnal Ilmu Pemerintahan, 2018)
The basic idea of this article is to examine the policy advocacy process on Winongo settlement arrangement riverbanks in Yogyakarta. Problems settlements along the river Winongo become increasingly critical as more densely populated to cause the symptoms of poverty and slums. This condition is then ignited the presence Arkom and FKWA to show arrangement ideas through policy advocacy process. Therefore, this article will focus on answering two things, there are how the coalition framework was formed and how the coalition manage their belief system, resources and strategies. To answer that questions above, this research was escorted by theory Advocacy Coalition Framework (ACF) of Sabatier and Jenkins Smith. Through the case study method, this research will explore the case of advocacy of policies Winongo settlement on the riverbanks. The results of the research shows that there are two coalitions in structuring settlements along the river Winongo, they are River coalitions and ?Right to the city? coalition. Both are proven to stand on two legs, as a member of the coalition and as a policy broker. This shows that the policy is not just a stage of systemic and technocratic, but the policy is a political process that allows each actor to act politically.